Study of Hepatic Dysfunction in Dengue Fever: Does it Tell You the Prognosis? - Kamath, Sangita; Ahmed, Tauheed (International Journal of Innovative Research in Medical Science, 2021)
Introduction: Dengue is the most rapidly spreading mosquito-borne viral disease. Liver is the most commonly affected organ and manifests as asymptomatic transaminitis to acute liver failure. Aim: (1) To study the clinical and biochemical profile of liver involvement. (2) To find the association between severity of hepatic dysfunction, morbidity and mortality in the admitted patients. Method and Material: This was a prospective study involving confirmed dengue fever cases admitted in Tata Main Hospital from January 2018 to December 2019. Cases were classified into non-severe dengue and severe dengue based on 2009 WHO classification. Severity of hepatic dysfunction was divided into grades A, B, C and D and correlation with various outcomes which included length of stay, complications and mortality was studied through relevant investigations. Results: Out of the 175 cases, Non-severe Dengue (NSD) was seen among 72.6% patients while severe dengue (SD) in 28.5% patients. Normal liver function was found in 68.6%, Grade B liver injury in 8% while Grade C and Grade D liver injury in 16.6% and 16.8% patients respectively. Mean AST levels were found to be higher than those of ALT levels. Longer hospital stay, complications like shock, acute kidney injury (AKI), thrombocytopenia and mortality were significantly more in patients with higher grades of liver dysfunction (p=0.03), while ARDS and MODS were seen only in patients with Grade C and Grade D liver injury. Conclusion: AST and ALT levels were statistically higher in Dengue fever patients with worse outcome. They can thus, serve as prognostic markers of severe Dengue.